ผลของการสอนซ่อมเสริมตามแนวทฤษฎีซ่อมแซมโดยใช้โปรแกรมคอมพิวเตอร์ ที่มีต่อมโนทัศน์และความคงทนในการเรียนคณิตศาสตร์ - ศศิวรรณ เมลืองนนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purposes of this research were: 1) to study mathematics concepts of seventh grade students being taught through the computer program in remedial teaching based of Repair theory; 2) to compare mathematics concepts of seventh grade students between groups being taught through the computer program in remedial teaching based on Repair theory and by using conventional remedial teaching; 3) to compare mathematics retentions of seventh grade students between groups being taught through the computer program in remedial teaching based on Repair theory and by using conventional remedial teaching. The population of this research was seventh grade students of secondary school under the Office of the Private Education Commission. The subjects were seventh grade students of Rajini School, Bangkok, in academic year 2006. They were divided into two groups, one experimental group with 43 students and one controlled group with 44 students. Students in the experimental group were taught through the computer program in remedial teaching based on Repair theory and those in the controlled group were taught by using conventional remedial teaching. The research instruments were the mathematics concepts test and the mathematics achievement test. The data was analyzed by means of arithmetic means, percentages, standard deviations and t-test. The results of this study were as follows: 1. Mathematics concepts of seventh grade students being taught through the computer program in remedial teaching based on Repair theory were higher than minimum criteria of 50 percents. 2. Mathematics concepts of seventh grade students being taught through the computer program in remedial teaching based on Repair theory were higher than those of students being taught by using conventional remedial teaching at. 05 level of significance. 3. Mathematics retentions of seventh grade students being taught through the computer program in remedial teaching based on Repair theory were not higher than those of students being taught by using conventional remedial teaching at .05 level of significance.